How do We Know Who Knows Who: An Empirical Assessment of Social Capital Usage for Turkish and Greek Cypriot Steel Manufacturing Industry Managers - Mustafa Sağsan; Nazım Adem Karasalih (Türk Kütüphaneciliği)
This paper is concerned with the social capital measurement of Turkish Cypriot and Greek Cypriot steel-manufacturing industry managers studied through the social network analysis method. The aim of this research undertaking is to find out the social capital usage of managers constructed on a relational basis. The comparative analysis between the two communities is conducted to understand to what extent Cypriot managers employed in steel-manufacturing companies fill in structural holes occurring in the Cypriot community. The epistemological dimension of this study is based on the anti-positivist paradigm.